Advancements in understanding the molecular mechanisms and clinical implications of Von Hippel-Lindau syndrome: A comprehensive review - Yaochun Wang; Jingzhuo Song; Shuxing Zheng; Shuhong Wang (Translational Oncology)
Von Hippel-Lindau Syndrome (VHL) is a rare genetic disorder characterized by tumors in multiple organs, including the kidneys, pancreas, and central nervous system. This comprehensive review discusses the genetic basis and clinical manifestations of VHL, as well as recent advancements in understanding the molecular mechanisms that lead to tumor formation. The authors highlight the role of hypoxia-inducible factors and the ubiquitin-proteasome system in VHL-associated cancer development .The review also discusses the potential clinical implications of these findings, such as the development of targeted therapies for VHL-associated cancers. However, the authors note the challenges associated with developing effective treatments for this complex disease, including limited patient availability for clinical trials due to its rarity .Overall, this review provides valuable insights into our current understanding of VHL and offers important avenues for future research aimed at improving the diagnosis, treatment, and management of VHL patients. By illuminating the molecular underpinnings of VHL-associated cancers, this work may ultimately help to develop more effective treatments and improve outcomes for patients with this challenging disease.